Método não destrutivo de estimativa da área foliar de plantas daninhas de ambiente aquático: tanner-grass e capim-fino - de Marchi, Sidnei Roberto; Martins, Dagoberto [UNESP]; da Costa, Neumarcio Vilanova (Universidade Estadual de Londrina (UEL), 2011)
The continuous inputs from agriculture areas and human or industrial sewer have been provided a widely demographic explosion of tropical tanner-grass and para grasss plants in the rivers and water reservoirs of Brazil. Considering the importance of these noxious weeds there is a vast necessity of basic studies on aspects related to reproduction, growing, development, nutritional requirements, responses to control systems and others. In most studies, leaf area knowledge is crucial and it is one of the most difficult characteristics to be measured because it usually requires expensive equipments or it uses a destructive technique. The objective of this work was to develop equations for leaf blade dimensional parameters to allow determination of the leaf area of African tanner-grass (Brachiaria subquadripara (Trin.) Hitchc) and para grass (Brachiaria mutica (Forsk.) Stapf.). Correlations between real leaf area and dimensional parameters of leaf blade such as length along the main vein (L) and maximum width (W) perpendicular to the main axis were studied. Only the linear equations allowed a good leaf area estimate. It is suggested to opt for a simple linear equation involving respective products of length times maximum width considering linear coefficient equal to zero. Thus, B. subquadripara (SS) and B. mutica (SM) non destructive leaf blade area estimates may be performed by the following formulas: SS = 0.7719 (L x W) and SM = 0.7479 (L x W), with coefficients of determination (R(2)) of 0.9594 and 0.9408, respectively.
Non-destructive method for surface leaf area estimate of weeds from aquatic environments: african tanner-grass and capim-fino
Keywords: Brachiaria subquadripara; Brachiaria mutica; biometry; leaf area